Proposta de utilização do quality function deployment (QFD) no sistema de análise de pontos críticos de controle (APPCC) na produção de refeições - Silva, Carlos Eduardo Sanches da; Gonçalves, Teresa Cristina Campos (Revista Gestão da Produção Operações e Sistemas, 2006)
The Hazard Analysis and Critical Control Point (HACCP) system has been utilized in Brazil since the 70s infood industries and catering services. This tool replaced the inspection of the final product, by identifying andcontrolling the steps of the production process of safe food. This paper proposes the use of the Quality FunctionDeployment (QFD) in the Hazard Analysis and Critical Control Point (APPCC) system, by means of aconceptual model. The QFD methodology provided subsidies for the identification of the potentialcontamination hazards in the generic process of production of meals. From the obtained results, the phases forthe production of meals, which demand a major attention from the workers, can be verified. The results of theprioritized items in the array could be used as a support in the selection and training process.Keywords: Food security; HACCP system; Quality function deployment.